The use of electronically designed games and their effectiveness in the achievement of mathematics among middle school students and the trend towards it (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify the use of electronically designed games and their effectiveness in:1) Achievement of first grade intermediate female students in mathematics.2) Attitudes of middle school students towards mathematics.